Readily Available Index of Insulin Sensitivity Is Associated with Metabolic Dysfunction-Associated Steatotic Liver Disease and Liver Fibrosis in Patients with Type 2 Diabetes - Stefano Ciardullo; Alessandro Roberto Dodesini; Emanuele Muraca; Pietro Invernizzi; Roberto Trevisan; Gianluca Perseghin (Diabetology)
Background/Objectives: Insulin resistance is a key factor in the development and progression of metabolic dysfunction-associated steatotic liver disease (MASLD), but accurately measuring it in patients with type 2 diabetes (T2D) remains challenging. This study examines the relationship between a recently proposed insulin resistance index and the presence of liver steatosis and fibrosis in individuals with T2D. Methods: This cross-sectional study utilized data from the 2017–2020 National Health and Nutrition Examination Survey. Patients with T2D who did not have chronic viral hepatitis or significant alcohol intake were included. The insulin sensitivity (IS) index was calculated using a formula incorporating body mass index, urine albumin-to-creatinine ratio, triglycerides, and gamma-glutamyl transferase. Liver stiffness and steatosis were assessed through transient elastography. MASLD was defined as a controlled attenuation parameter (CAP) of ≥274 decibels/meter (dB/m), while significant liver fibrosis was defined as a liver stiffness measurement (LSM) of ≥8 kPa. Multivariable logistic regression models, adjusted for potential confounders, were used to evaluate the association between IS and these liver outcomes. Results: A total of 1084 patients with T2D were analyzed. The prevalence of MASLD and significant liver fibrosis was 74.1% (95% CI 68.7–78.9) and 25.4% (95% CI 21.2–30.2), respectively. After adjusting for age, sex, waist circumference, and race/ethnicity, lower IS scores (indicating higher insulin resistance) were independently associated with increased odds of both MASLD (quartile 1 vs. quartile 4: OR 2.66, 95% CI 1.23–5.71) and significant liver fibrosis (quartile 1 vs. quartile 4: OR 3.30, 95% CI 1.45–7.51). These findings remained consistent across subgroups stratified by age, sex, and obesity status. Conclusions: This novel IS model, derived from commonly available clinical and biochemical markers, is independently associated with liver steatosis and fibrosis. Its application may help identify patients with more advanced MASLD, facilitating early intervention and risk stratification.